Changes in cardiac biomarkers in association with alterations in cardiac structure and function, and health status in heart failure with reduced ejection fraction: the EVALUATE‐HF trial. (30th May 2022) - Myhre, Peder L.; Claggett, Brian L.; Shah, Amil M.; Prescott, Margaret F.; Ward, Jonathan H.; Fang, James C.; Mitchell, Gary F.; Solomon, Scott D.; Desai, Akshay S.
Abstract : Aims: N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), cardiac troponin T (cTnT) and soluble ST2 (sST2) provide complementary prognostic information in heart failure with reduced ejection fraction (HFrEF). We aimed to assess the association between changes in these markers with changes in cardiac structure, function and health status. Methods and results: Patients in the EVALUATE‐HF trial ( n = 464) were randomized to sacubitril/valsartan or enalapril for 12 weeks, followed by 12‐week open‐label sacubitril/valsartan. Cardiac biomarkers, echocardiography, and Kansas City Cardiomyopathy Questionnaires (KCCQ) were completed at baseline, and after 12 and 24 weeks. A total of 410 patients (88%) had serial biomarker measurements available (mean age 67 ± 9 years, 75% male and 75% white). After 24 weeks of treatment, NT‐proBNP, sST2 and cTnT decreased by median (Q1, Q3) −31% (−55%, +6%), −6% (−19%, +8%) and − 3% (−13%, +8%), respectively (all p < 0.001). Decreases in NT‐proBNP were associated with reductions in cardiac volumes and improvements in systolic and diastolic function and health status. Decreases in cTnT were associated with reductions in left ventricular mass, but not with changes in left ventricular function or KCCQ. Decreases in sST2 were consistently associated with improvements in health status, but not with measures of cardiac structure or function. There was no effect modification from treatment on the associations investigated ( p for interaction >0.05) Conclusion: In HFrEF, serial changes in NT‐proBNP correlate with changes in several key measures of cardiac structure and health status. cTnT changes correlate with changes in left ventricular mass and sST2 with changes in health status. These data highlight possible complementary pathophysiologic implications of changes in NT‐proBNP, cTnT and sST2. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT02874794. Abstract : Changes from baseline to week 24 in quartiles of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), soluble ST2 (sST2) and cardiac troponin T (cTnT), and the association with changes in measures of cardiac structure and health status. P ‐values are for trends across quartiles and adjusted for age, sex, race, body mass index, New York Heart Association class, estimated glomerular filtration rate and baseline value of each exposure and outcome variable. KCCQ‐OS, Kansas City Cardiomyopathy Questionnaire overall summary; LA, left atrial; LV, left ventricular.